Feminist critique of bioeconomies: paradigm struggles toward a caring economy - Christa Wichterich (Sustainability: Science, Practice, & Policy)
This article addresses the tension between green productivism and reproductivity of human and non-human life from a critical feminist perspective. It recalls feminist spaces and strategies of critique and resistance against biotechnologies and bioeconomies: (1) the Chipko movement of the 1970s in defense of life and livelihoods, and ecofeminists principles, (2) the “right to say no” and paradigm struggles against capitalist and neocolonial extractivisms, (3) care and its transformative potential toward degrowth, and, finally, (4) critique of digital and artificial intelligence (AI) fixes in bioeconomy. This analytical recalling and compilation work brings together feminist economic and ecological thinking and agency starting with resistance against dispossession and commodification of natural resources and ending in paradigm struggles around the extractivist neocolonial growth model. Furthermore, categories of feminist critique of techno-sciences help to deconstruct power relations, violence and path dependency of western sciences, and knowledge creation, including modern biotechnologies which are deeply imbued by strategies of domination of the “other” and of economization. The critical feminist repertoire confronts the green productivism, the extractivism, and the techno-solutionism of the technology-intensive bioeconomy, while the practical alternatives open new socio-transformative avenues toward a caring economy and interdependent reciprocal society-nature relation as well as they undermine the narrative that there is no alternative.